KONSEP PENDIDIKAN HASYIM ASY’ARI; TIPOLOGI DAN RELEVANSINYA TERHADAP PARADIGMA PENDIDIKAN INDONESIA EMAS 2045 - Bahri, Rosidi; Fuad, Ah. Zakki; Bakar, M. Yunus Abu (Universitas Al-Amien Prenduan, 2024)
AbstractHasyim Asy'ari is better known as a cleric who transformed Islamic boarding school education, as well as being a fighter. Hasyim Asy'ari turned Tebuireng into a model Islamic boarding school for Islamic boarding schools throughout Indonesia. By using relevant literature data from the book Adab al-Alim wa al-Muta'allim by Hasyim Asy'ari, this research uses library research by collecting information through documentary methods. In the book Directions for Competency of the Indonesian Generation Towards a Golden Indonesia 2045 prepared by the National Education Standards Agency (BNSP), Indonesia will celebrate its 100th anniversary of independence in 2045. Indonesia will experience a golden age at that time. Education needs to be organized as a